Limits to CBA in UK and European environmental policy: Retrospects & future prospects - R. Kerry Turner (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2006)
This paper reviews the contemporary debate and the now long standing role of CBA in UK and European environmental policy appraisal and looks forward to possible future applications. The position taken is that despite its limitations CBA still has an important part to play in environmental policy appraisal. However, with the increasingly 'contested' nature of environmental and related public policies and outcomes, its role will become less prescriptive and its findings more constrained by social justice and ethical imperatives. Future CBA is more likely to continue to flourish as a component in a wider policy analysis and decision support system. Whatever decision support system is eventually adopted, its value will be judged on how well it aids real policymakers operating iteratively in the non-linear real world political economy.
Keywords: 330; cost-benefit analysis; environmental policy; valuation; Kosten-Nutzen-Analyse; Umweltpolitik; Wirkungsanalyse; Großbritannien; EU-Staaten